2006
DOI: 10.1002/mrm.20839
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory data analysis reveals visuovisual interhemispheric transfer in functional magnetic resonance imaging

Abstract: We used an exploratory data analysis approach to detect interhemispheric processing of complex visual stimuli in functional magnetic resonance imaging (fMRI). A crossed-uncrossed visual field paradigm was used to elicit interhemispheric transfer of picture/word information. Under the uncrossed (control) condition, the stimuli were presented to the preferential hemispheres (pictures to the left visual field/right hemisphere and words to the right visual field/left hemisphere). Under the crossed condition, the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 20 publications
1
39
0
Order By: Relevance
“…The Poffenberger task was completed with a mean accuracy of 97.5%. 3 The mean reaction time of the motor cross condition (413.9 ms, SD = 73.8 ms) was longer than the mean reaction time in the uncrossed condition (351.7 ms, SD = 53.6 ms). The mean crossed-uncrossed difference was 62.2 ms, which was statistically significant (p < 0.001).…”
Section: Behavioral Resultsmentioning
confidence: 81%
“…The Poffenberger task was completed with a mean accuracy of 97.5%. 3 The mean reaction time of the motor cross condition (413.9 ms, SD = 73.8 ms) was longer than the mean reaction time in the uncrossed condition (351.7 ms, SD = 53.6 ms). The mean crossed-uncrossed difference was 62.2 ms, which was statistically significant (p < 0.001).…”
Section: Behavioral Resultsmentioning
confidence: 81%
“…In spite of the bias against it, a growing body of evidence supports fMRI in WM regions (Omura et al, 2004;Weber et al, 2005;D'Arcy et al, 2006;Mazerolle et al, 2008;Gawryluk et al, 2009Gawryluk et al, , 2011Yarkoni et al, 2009;Mazerolle et al, 2010;Fabri et al, 2011). Recent findings can be attributed to known energy-dependent processes in WM (Tettamanti et al, 2002;Mazerolle et al, 2008).…”
Section: Introductionmentioning
confidence: 89%
“…In order to elicit WM activation, many studies have examined interhemispheric transfer (IHT) across the corpus callosum (e.g., D'Arcy et al, 2006;Mazerolle et al, 2008). Tasks typically involve rapid presentation of stimuli to a visual field, with contralateral motor responses.…”
Section: Introductionmentioning
confidence: 99%
“…Such tasks, in which functionally lateralized stimuli (words and faces) are presented to the right and left visual hemifields, have been used to study disconnection syndromes in split brain patients (Gazzaniga, Bogen, and Sperry, 1965) and have been previously developed for fMRI (D'Arcy et al, 2006). Mazerolle et al (2008) reported activation in the isthmus of the corpus callosum in 21% of individuals.…”
Section: Introductionmentioning
confidence: 99%